2003
DOI: 10.2337/diabetes.52.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-Induced, Progressive Endometrial Involution Characterization of Periluminal Epithelial Lipoatrophy

Abstract: The present studies detail the cytopathological alterations in uterine epithelial, basal lamina, and stromal endometrial subregions, and associated endocrine parameters that occur during the progressive exacerbation of the diabetes syndrome in this species of mouse. These alterations result in a cellular lipoatrophic condition that compromises uterine tissue integrity and promotes reproductive involution. Uterine tissue samples were obtained from litter-matched control (؉/?) and diabetic (db/db) C57BL/KsJ mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(92 citation statements)
references
References 25 publications
1
89
0
1
Order By: Relevance
“…One study performed in 2003 [34] revealed that there were considerable epithelial changes in diabetic rats. In another study on effects of progressive hyperglycemia on the endometrium, a thickened basal membrane, phagocytic blood elements extending into the basal membrane, differentiation in the stromal cells, vacuolization and degeneration were observed [35].…”
Section: Discussionmentioning
confidence: 99%
“…One study performed in 2003 [34] revealed that there were considerable epithelial changes in diabetic rats. In another study on effects of progressive hyperglycemia on the endometrium, a thickened basal membrane, phagocytic blood elements extending into the basal membrane, differentiation in the stromal cells, vacuolization and degeneration were observed [35].…”
Section: Discussionmentioning
confidence: 99%
“…1A). Although it may be difficult to compare body weights between the ICR and C57BL/6 mice, early onset obesity can be observed in ob/ob and db/db mice by 5-7 wk of age (19,31), in contrast to the development of obesity in fat/fat and tub/tub mice at 6 -8 and 10 wk of age, respectively (10). Regarding maximum body weight, the Daruma mice were more similar to ob/ob and fat/fat mice, which attain a weight of 60 -70 g, than to db/db and tub/tub mice, which attain a final body weight of 50 -60 g (10,38,40).…”
Section: E459mentioning
confidence: 99%
“…Suppression of normal reproductive cyclicity, folliculogenesis, ovarian steroid synthesis and release, ovulation, corpus luteum formation and associated endocrine parameters during diabetic states promotes endometrial involution and atrophy [1,3,[8][9][10]. Ultimately, the consequences of the diabetes-associ-ated endopathological and metabolic alterations induce reproductive incompetence and organoatrophy of the female reproductive tract [1,8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Genetically diabetic (db/db) mutant C57BL/KsJ mice have been utilized as an experimental model for the evaluation of the progressive cytopathological changes in endometrial tissue which occur as a result of the nonhomeostatic diabetic metabolic environment [1,8,10]. Of particular interest have been the descriptions of the progressive intracytoplasmic accumulation of triglyceridefree fatty acid pools that accumulate at the cytobasal pole of endometrial epithelial cells [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation